DETRIMENTAL EFFECTS OF PESTICIDES ON HEALTH AND ENVIRONMENT - KHALID MAHMOOD CHAUDHARY, SHAFIQ UR REHMAN ZIA, IJAZ ASHRAF; TALIB, UMAIR; AHMAD, IRFAN (Journal of Ecobiotechnology, 2017)
Pesticides are toxic chemicals used for controlling of insects and pests which caused harms to plants or animals. Pesticides also effect the environment as well as human health. They play a vital role in securing of food but they require a number of risks and problems. Therefore, present study is designed to know the pesticide usage and its harmful effects on environment and health of cotton growers. There are 19 rural union councils out of which 4 were selected through simple random sampling. From each selected union council, 2 villages were selected at random and from each selected village, 20 cotton growers were selected randomly thus making a sample size of 160 respondents. A well planned pre-tested and validated interview schedule was prepared for the collection of data from the selected respondents. The collected data were examined by using Statistical Package for Social Sciences (SPSS) for illustration conclusions and making recommendations. A vast majority (90%) of the respondents selected the pesticides on better results, (83.1%) on behalf of multinational company and majority (76.3%) selected pesticides of national company and a significant of majority (70%) of respondents used the gloves whereas a huge majority (85.6%) of respondents weared the mask during pesticide application. It was found that a huge majority (81.9%) of respondents had headache effect, 67.1% had fatigue, and majority (68.8%) had dizziness while 68.1% had skin disorders. Govt. should promote the first aid training program for safety measurement regarding pesticide usage and enhance the protection techniques for environment and health of organisms regarding pesticides effect.